Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s10653-020-00739-4
|View full text |Cite
|
Sign up to set email alerts
|

As(III) adsorption onto Fe-impregnated food waste biochar: experimental investigation, modeling, and optimization using response surface methodology

Abstract: Biochar derived from food waste was modified with Fe to enhance its adsorption capacity for As(III), which is the most toxic form of As. The synthesis of Fe-impregnated food waste biochar (Fe-FWB) was optimized using response surface methodology (RSM), and the pyrolysis time (1.0, 2.5, and 4.0 h), temperature (300, 450, and 600°C), and Fe concentration (0.1, 0.3, and 0.5 M) were set as independent variables. The pyrolysis temperature and Fe concentration significantly influenced the As(III) removal, but the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…Food waste was collected as a raw material for biochar from a processing facility located in Seoul, South Korea [47]. At the facility, the food waste collected at household level was subjected to steam boiling at 150 • C followed by crushing and sieving.…”
Section: Preparation Of Al-fwbmentioning
confidence: 99%
“…Food waste was collected as a raw material for biochar from a processing facility located in Seoul, South Korea [47]. At the facility, the food waste collected at household level was subjected to steam boiling at 150 • C followed by crushing and sieving.…”
Section: Preparation Of Al-fwbmentioning
confidence: 99%
“…Due to the impact of production and other wastewater treatment processes, some industrial wastewater may contain lots of ions, e.g., Ca 2+ , Na + and Cl − [29]. Therefore, ionic strength is also an important factor affecting the removal of Cr(VI).…”
Section: Effect Of Coexisting Ions In Solutionmentioning
confidence: 99%
“…After pyrolysis, these inorganic metal salts adhere to the surface of the biochar via the formation of metal oxide nanoparticles, thus improving the adsorption capacity of the biochar (Tan et al 2016). Previous studies have reported that metal-impregnated biochar is effective for anions, such as selenate (Hong et al 2020, Lee et al 2021), uoride (Mei et al 2020, Meilani et al 2021, arsenate (Lyonga et al 2020), chromate (Dong et al 2011), and phosphate (Kang et al 2021). Food waste (FW), separately collected at the household level in Korea, can be used more e ciently for biochar production than sewage sludge with hazardous heavy metals (Hong et al 2020).…”
Section: Introductionmentioning
confidence: 99%